DEGRADASI SENYAWA DIKOFOL DALAM PESTISIDA KELTHANE 200 EC SECARA FOTOLISIS DENGAN PENAMBAHAN TiO2-ANATASE - Safni -; Desmiati -; Hamzar Suyani (Jurnal Riset Kimia, 2009)
ABSTRACT This research is conducted to know whether dicofol compound in Kelthane 200 EC pesticide can be degraded with photolysis method by adding TiO2-anatase. Photolysis method is conducted by using UV 10 watt lamp at the wavelength of 365 nm. The result shows that photolysis method could degrade the dicofol compound at 30 mg/L concentration as 9.73% after 60 minutes irradiation. Paraquat compound with the similar concentration by adding 30 mg unmixed TiO2-anatase could degradade 32.51% after 60 minutes irradiation and 65.84% by mixing TiO2-anatase. Furthermore, dicofol with the same concentration and TiO2-anatase addition could 86.13% after 180 minutes irradiation. Keywords : degradation, photolysis, dicofol, anatase-TiO2